Hearing Loss Detection in Schools and Early Child Care Settings: An Overview of School-Age Hearing Screening Practices. (September 2016) - Winston-Gerson, Randi; Sabo, Diane L.
The school nurse is the key figure in successful school screening programs. A student with unidentified and unmet health care needs is unlikely to perform at their full potential, both academically and socially. The purpose of the article is to serve as a resource, providing guidance, strategies, and a discussion of available equipment to assist with successful screening programs.